2016
DOI: 10.1016/j.jgr.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus-dependent cognitive enhancement induced by systemic gintonin administration

Abstract: BackgroundA number of neurological and neurodegenerative diseases share impaired cognition as a common symptom. Therefore, the development of clinically applicable therapies to enhance cognition has yielded significant interest. Previously, we have shown that activation of lysophosphatidic acid receptors (LPARs) via gintonin application potentiates synaptic transmission by the blockade of K+ channels in the mature hippocampus. However, whether gintonin may exert any beneficial impact directly on cognition at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…5a). Moreover, there was no difference in the discrimination ratio (F [3,34] = 0.775, p = 0.516; Fig. 5b).…”
Section: Oral Administration Of Gintonin Alleviates Object Location Mmentioning
confidence: 85%
See 2 more Smart Citations
“…5a). Moreover, there was no difference in the discrimination ratio (F [3,34] = 0.775, p = 0.516; Fig. 5b).…”
Section: Oral Administration Of Gintonin Alleviates Object Location Mmentioning
confidence: 85%
“…5c). Furthermore, there was a significant difference in the discrimination ratio (F [3,34] = 5.238, p = 0.004; Fig. 5d), and post hoc comparisons revealed that the D-gal + gintonin (100 mg/kg, p.o.…”
Section: Oral Administration Of Gintonin Alleviates Object Location Mmentioning
confidence: 90%
See 1 more Smart Citation
“…Although when combined with other AD drugs it may improve the cognitive functions in AD patients (13). Gintonin which is relatively a new component of ginseng was found to improve memory formation in mice when administered systemically (14).…”
Section: Treatment For Degenerative Disordersmentioning
confidence: 99%
“…22) Fourth, Kim et al observed that hippocampal long-term potentiation (LTP) increased in mice that were previously treated with gintonin for 7 d orally compared to saline-treated mice. 24) In addition, the hippocampi of mice that were previously treated for 7 d with gintonin showed increased expressions of learning and memory-related proteins such as phosphorylated cAMP-response element binding (pCREB) protein and brain-derived neurotrophic factor (BDNF). Finally, in a behavioral study, gintonin administration improved fear memory retention in the contextual fear-conditioning test in mice.…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 99%